Beginning Microsoft Excel 2010 - Katz, Abbott (Apress, 2012)
Welcome to Beginning Microsoft Excel 2010. No; you’re not a dummy, but you may be new to this vast, empty, rectangular world of columns and rows that Excel spreadsheets comprise, and you may be just a little bit intimidated, too. You may have a couple of questions as result: What do I do, where, and how? Those are big questions, and the answers to them don’t come in the 25-words-or-less variety; but Beginning Microsoft Excel 2010 tries to make the answers easier to understand by erring on the side of explanation over the click-here, click-there, bullet-pointed mode of book instruction. Knowing what’s going on in your workbook, and why, makes the prospect of constructing this, and your next, workbook that much less daunting. Beginning Microsoft Excel 2010 isn’t to be read as a spreadsheet “bible,” the kind of work that catalogues each and every command the application has to offer. That kind of book surely has its place, of course, but if you’re starting out with Excel — and I’m speaking as an Excel instructor — you need to know the important basics, and then some — those capabilities which can get you up and running and doing real work, and pretty soon. As a result, and given the proverbial limitations of space, a good many decisions had to be made along the way about what to omit, as well as what to include. Excel is, after all, a vast application, and something tells me you’re not prepared to pay for a few thousand pages worth of detail about the whole shebang